(untitled) (Conferencea, 2023)
The article considers one of the factors influencing the process of processing kinematic threads and contributing to the reduction of the error in the manufacture of threads - the value of the allowance to be removed. Basically, we will talk about the allowance for final processing, where all accuracy parameters must be observed.